ANALYSIS OF IMPLEMENTATION OF INCLUSIVE EDUCATION POLICY FOR STUDENTS WITH SPECIAL NEEDS IN REGULAR SCHOOLS IN LEBAK DISTRICT - Risma; Dedi Mulia; Neti Asmiati (PT. Jurnal Center Indonesia Publisher, 2025)
Inclusive education for students special needs at the level School Reduler in Lebak Regency . This study uses a qualitative approach descriptive with technique data collection through interviews , observations , and documentation . Informants in this study included the Head of Regular Education , Head of Quality Improvement Section , Principal , and Special Assistant Teacher (GPK). The results of the study show that implementation policy education inclusion in Lebak Regency is still face challenges , such as limitations power competent educators , lack of training , lack of facility supporters , as well as low understanding public to education inclusion . Recommendation This research includes the need for improvement teacher training , provision facility adequate education , and strengthening collaboration between stakeholders policy so that policy education inclusion can implemented optimally.